Biophysical characterization of protein-protein interactions with mass photometry - Soltermann, F (2020)
Interactions between biomolecules control the processes of life in health and their malfunction in disease, making their characterization and quantification essential. We first explore the capabilities of established methods for binding affinity measurements of protein-protein interactions and present mass photometry in this context. We explain that immobilization- and label-free analytical techniques are desirable because of their simplicity and minimal invasiveness, but that they struggle with quantifying tight interactions and resolving co-existing species.